Sustainable - Lifelong Learning in Transit from TVET to the University: A Recognition of Prior Learning Phenomenon - Masoabi, Charles S (European Journal of Sustainable Development, 2023)
This study seeks to explore the application of recognition of prior learning (RPL) process on N6 students from Technical and vocational education and training (TVET) at the university of technology (UoT). In the context of this study RPL is seen as a vehicle that promotes lifelong learning for sustainable development among youth. The researcher employs case study design situated in qualitative research approach. The target group of participants are heads of departments (HODs) in the UoT from faculties that render similar studies as those found in the neighbouring TVET college. The HODs are the custodians of admission process. Open-ended question online survey will be developed on Question-pro and emailed to the respective HODs for their response. Content analysis will also be used on documents such as institutional and the department of higher education (DHET) RPL policies. The study revealed that the RPL process is a lengthy and costly exercise, and there are no funds dedicated to the assessment process. Although the institution under study has RPL policy, it is rather inadequate to guide HODs in promotion of lifelong learning for sustainable development of human resources. Keywords: Recognition of prior learning, lifelong learning for sustainable development, TVET.